Factors Influencing Second and Third Dose Observance during Seasonal Malaria Chemoprevention (SMC): A Quantitative Study in Burkina Faso, Mali and Niger - Anyirékun Fabrice Somé; Issaka Zongo; Issaka Sagara; Alkassoum Ibrahim; Césaire Damien Ahanhanzo; Edoh Eddie Agbanouvi-agassi; Dona Alain Sayi; Lea Pare Toe; Zachari Kabré; Frédéric Nikiéma; Thomas Bazié; Sylvin Ouédraogo; et al. (Tropical Medicine and Infectious Disease, 2022)
This study aims to evaluate the factors influencing the adherence to the 2nd and 3rd doses of Amodiaquine (AQ) during seasonal malaria chemoprevention (SMC) in Burkina Faso, Mali, and Niger. Overall, 3132 people were interviewed during surveys between 2019 and 2020 in 15 health districts. In Burkina Faso, Mali, and Niger, the proportions of non-adherence were 4.15%, 5.60%, and 13.30%, respectively, for the 2nd dose and 3.98%, 5.60% and 14.39% for the 3rd dose. The main cause of non-adherence to the 2nd and 3rd doses was other illnesses in 28.5% and 29.78%, respectively, in Burkina Faso, 5.35% and 5.35% in Mali and 1.6% and 0.75% in Niger. It was followed by vomiting in 12.24% and 10.63% for Burkina and 2.45% and 3.78% in Niger. The last cause was refusal in 6.12% and 4.25% in Burkina, 33.9% and 15.25% in Mali and 0.8% and 1.51% in Niger. Non-adherence of doses related to parents was primarily due to their absence in 28.5% and 27.65% in Burkina, 16.07% and 16.07% in Mali and 7.37% and 6.06% in Niger. Traveling was the second cause related to parents in 12.24% and 12.76% in Burkina, 19.64% and 19.64% in Mali and 0.81% and 0.75% in Niger. Non-adherence related to community distributors was mainly due to missing the doses in 4.08% and 4.25% in Burkina, 23.21% and 23.21% in Mali, 77.04% and 76.51% in Niger. Our study reported very small proportions of non-adherence to 2nd and 3rd doses of SMC and identified the main causes of non-adherence. These findings will provide helpful information for policymakers and public health authorities to improve adherence to SMC